Genomic epidemiology of Vibrio cholerae during a mass vaccination campaign of displaced communities in Bangladesh - Alyce Taylor-Brown; Mokibul Hassan Afrad; Ashraful Islam Khan; Florent Lassalle; Md. Taufiqul Islam; Nabid Anjum Tanvir; Nicholas R. Thomson; Firdausi Qadri (Nature Communications, 2023)
Abstract Ongoing diarrheal disease surveillance throughout Bangladesh over the last decade has revealed seasonal localised cholera outbreaks in Cox’s Bazar, where both Bangladeshi Nationals and Forcibly Displaced Myanmar Nationals (FDMNs) reside in densely populated settlements. FDMNs were recently targeted for the largest cholera vaccination campaign in decades. We aimed to infer the epidemic risk of circulating Vibrio cholerae strains by determining if isolates linked to the ongoing global cholera pandemic (“7PET” lineage) were responsible for outbreaks in Cox’s Bazar. We found two sublineages of 7PET in this setting during the study period; one with global distribution, and a second lineage restricted to Asia and the Middle East. These subclades were associated with different disease patterns that could be partially explained by genomic differences. Here we show that as the pandemic V. cholerae lineage circulates in this vulnerable population, without a vaccine intervention, the risk of an epidemic was very high.